ANALISIS MINAT BELI KONSUMEN DI ERA PANDEMI COVID-19 UNTUK MENINGKATKAN VOLUME PENJUALAN - Rahmawati, Eka Dian; Muslih, Basthoumi (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2021)
The development of the business world today is never separated from competition, entrepreneurs are required to always be creative and innovate to be able to maintain the business that has been built. The purpose of this study was to analyze and determine consumer buying interest at Srikandi Gold Jewelery Shop from the Attention and Interest Indicators. The approach in this study uses a qualitative approach with data collection techniques with interviews. The data analysis technique uses data reduction, data presentation, and conclusion drawing. The data sources used are primary data sources and secondary data sources. The conclusions of this study are (1) The decline in sales in the first semester and an increase in sales in the final semester. (2) The difference in sales in the first semester is 2,495,560 gr, while sales in the last semester are 3,454,150 gr. Recommendations for Srikandi Gold Jewelry Stores are to continue to comply with government recommendations, continue to provide prices below other stores, give bonuses to jewelry purchases, and provide the latest jewelry models to increase sales volume. Keywords: buying interest, covid-19 pandemic, sales volume